Rifins: A second family of clonally variant proteins expressed on the surface of red cells infected with Plasmodium falciparum - Kyes, Sue A. (The National Academy of Sciences, 1999)
Many pathogens evade the host immune response or adapt to their environment by expressing surface proteins that undergo rapid switching. In the case of Plasmodium falciparum, products of a multigene family known as var are expressed on the surface of infected red cells, where they undergo clonal antigenic variation and contribute to malaria pathogenesis by mediating adhesion to a variety of host endothelial receptors and to uninfected red blood cells by forming rosettes. Herein we show that a second gene family, rif, which is associated with var at subtelomeric sites in the genome, encodes clonally variant proteins (rifins) that are expressed on the infected red cell surface. Their high copy number, sequence variability, and red cell surface location indicate an important role for rifins in malaria host–parasite interaction.